Visuo-motor delay, information-movement coupling, and expertise in ball sports - Le Runigo, C.; Benguigui, N.; Bardy, B. G. (Journal of Sports Sciences, 2010)
We compared the performance of tennis experts and non-experts using a simulated interceptive task, in which the ball could be unexpectedly deviated 400 ms before contact. The results showed that experts were more accurate than non-experts when intercepting balls that deviated in their trajectory and that this could be explained by their shorter visuo-motor delay in adapting their interceptive movement. In addition, multiple regression analyses revealed that visuo-motor delay was a good predictor of accuracy in this task. Finally, accuracy in the simulated interceptive task was shown to be a reasonable predictor of expertise in tennis assessed by national ranking. In combination, the present results suggest that an important component of expertise in interceptive skills is fast information-movement coupling, which corresponds to a reduced delay in integrating vision and action. Our findings highlight the potential of the virtual interceptive task used here to predict performance in tennis.